Policy Recommendation for the Conservation of the Suweon Treefrog (Dryophytes suweonensis) in the Republic of Korea - Borzée, Amaël; Jang, Yikweon (Frontiers in Environmental Science, 2019)
The Suweon treefrog (Dryophytes suweonensis) is an endangered species with an important evolutionary significance. However, the current rate of decline projects the extinction of the species within a few decades in the Republic of Korea. The species is presently exclusively inhabiting rice paddies and is not present in any protected area, although it would be relatively easy to designate protected area under the RAMSAR convention and correct the current negative population dynamics. Through three policy recommendations, we present the points of importance for the conservation of the Suweon Treefrog, list the site of importance for its conservation, and introduce an agricultural model allowing for the conservation of the species as well as continued rice production and economic income. Actionable recommendations: - Establishment of protected areas within the range of D. suweonensis - Pesticide and herbicide ban in rice-paddy complexes where D. suweonensis occurs - Vegetation mowing limit for surroundings of rice paddies where D. suweonensis occurs.